Mixing state evolution of agglomerating particles in an aerosol chamber: Comparison of measurements and particle-resolved simulations. Issue 11 (2nd November 2019) - Shou, Chenchao; Riemer, Nicole; Onasch, Timothy B.; Sedlacek, Arthur J.; Lambe, Andrew T.; Lewis, Ernie R.; Davidovits, Paul; West, Matthew
Abstract: This article presents a validation study of the stochastic particle-resolved aerosol model PartMC with experimental data from an aerosol chamber experiment. For the experiment, a scanning mobility particle sizer and a single-particle soot photometer were used to monitor the aerosol mixing state evolution of two initially externally mixed aerosol populations of ammonium sulfate and black carbon particles undergoing agglomeration. We applied an efficient optimization algorithm (ProSRS) to determine several unconstrained simulation parameters and were able to successfully reproduce number concentrations and size distributions of mixed particles that formed by agglomeration. The PartMC modeling approach in conjunction with the optimization procedure provides a tool for detailed comparisons of chamber experiments and modeling, where aerosol mixing state is the focus of investigation. Copyright © 2019 American Association for Aerosol Research